Phytolith analysis at the Neolithic tell Vrbjanska Čuka in Pelagonia (North Macedonia) - Budilová, Kristýna (Jihočeská univerzita, 2023)
The thesis deals with an analysis of phytoliths, microscopical residues of plants. The analysis was applied in order to gain a new archaeobotanical data on the Neolithic period at the archaeological site Vrbjanska Čuka in Pelagonia, North Macedonia. The results brought new insights into a plant management and related activities on the site, as well as contributed to an understanding of a past environment of the early agricultural society.
Phytolith analysis at the Neolithic tell Vrbjanska Čuka in Pelagonia (North Macedonia)
Keywords: phytoliths; archaeobotany; Neolithic; Balkans; phytoliths; archaeobotany; Neolithic; Balkans